Reconciliatory Aesthetic and Doctrinal View of Rwanda, (Saarbrücken: Lap Lambert Academic Publishing, 2013). (Hekima Review, 2014)
Reconciliatory Aesthetic & Doctrinal View of Rwanda 1994 came as Rwanda remembered the 20th anniversary of the Genocide that claimed more than 800.000 lives in only one hundred days. This devastating tragedy of our recent world history challenges human beings, especially Christians, to rethink the meaning of being human and the relationship between Revelation, Redemption and Christian praxis. Emmanuel Foro unearths the roots of the paradoxical “escalation of violence in a century of increasing mastery of human mind over nature and realms beyond our planet”, unfortunately, in a more than 80% Christian country. The 1994 Rwandan genocide raises questions about the process of evangelization of Rwanda and leaves one wondering how this absurdity of violence and human cruelty fits in the plan of God’s self-Revelation, Redemption and Salvation of humanity.